Georgia Country Environmental Analysis : Institutional, Economic, and Poverty Aspects of Georgia’s Road to Environmental Sustainability - World Bank (Washington, DC, 2015)
During the past decade, Georgia’s pursuit of economic reforms led to impressive economic growth, capital inflow, and investments. It helped improve the business environment and infrastructure, strengthened public finances, and liberalized trade. Georgia achieved most of the human development targets of the Millennium Development Goals (MDGs). This progress did not result, however, in improved environmental governance or better management of natural resources. Nowadays, environmental policies are receiving increasing attention from Georgian policy and decision makers, recognizing that sustainable development is about a profound change of policies that drive systemic transformation of production, consumption, and behavioral patterns. The list of the country’s environmental challenges is long. Current policies and instruments lack the rigor to effectively reduce pressures on natural assets and protect public health from poor environmental quality. Georgia does not have a comprehensive assessment of the cost of inaction to environmental degradation linking it to economic growth, poverty, and shared prosperity. This is a central issue on which the Country Environmental Analysis (CEA) is focused. The main objective of the CEA is to assist the government, civil society, and development partners of Georgia in identifying and analyzing critical environmental constraints to sustainable growth and shared prosperity. Georgia’s Country Partnership Strategy for 2014-2017 points to lagging public policies on protecting the environment and natural resources, against impressive economic growth. It further highlights several areas needing attention, such as air and water quality, waste management, land and landscape management, and nature resource use and protection.